Interdisciplinary approach for congenitally missing incisor with orthodontics and dental implant: Case Series - Gupta, Gaurav; Gupta, D. K.; Gupta, Priyanka; Rana, Kuldeep Singh; Sankhla, Devanshi (Journal of Orofacial Research, 2022)
Interdisciplinary approaches for congenitally missing teeth, which are frequently presented to the dentist, need a proper treatment plan. Prosthodontic fixed and removable prosthesis, orthodontic movement of maxillary canine to the lateral incisor site and single tooth implants, resin-bonded retainers are the various treatment modalities present to replace congenitally missing teeth. When treating the anterior maxilla, especially in the replacement of missing teeth, the important factors which need to be considered is careful treatment planning, space management, augmentation of bone and proper details of implant surgical and prosthetic techniques is required. This case report addresses fundamental considerations related to replacement of congenitally missing upper incisors by a team approach. A combined orthodontic and implant placement treatment approach can give an improved functioning occlusion with favorable aesthetics.